2020
DOI: 10.3390/ijms21207699
|View full text |Cite
|
Sign up to set email alerts
|

Constructing 3-Dimensional Atomic-Resolution Models of Nonsulfated Glycosaminoglycans with Arbitrary Lengths Using Conformations from Molecular Dynamics

Abstract: Glycosaminoglycans (GAGs) are the linear carbohydrate components of proteoglycans (PGs) and are key mediators in the bioactivity of PGs in animal tissue. GAGs are heterogeneous, conformationally complex, and polydisperse, containing up to 200 monosaccharide units. These complexities make studying GAG conformation a challenge for existing experimental and computational methods. We previously described an algorithm we developed that applies conformational parameters (i.e., all bond lengths, bond angles, and dihe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 135 publications
(222 reference statements)
5
29
1
Order By: Relevance
“…The binding of AT III to heparin requires an absolute 2 S 0 conformation, but according to the NMR structure information, there is negligible 1 C 4 conformation in the whole binding process ( Guerrini et al, 2006 ). Even though IdoA brings more variable binding conformational selectivity, recent studies have shown that GlcA has a better effect on the overall conformation of GAGs ( Whitmore et al, 2020 ). In order to adapt to the ECM environment, the angle of the glycosidic linkages is allowed to change to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of AT III to heparin requires an absolute 2 S 0 conformation, but according to the NMR structure information, there is negligible 1 C 4 conformation in the whole binding process ( Guerrini et al, 2006 ). Even though IdoA brings more variable binding conformational selectivity, recent studies have shown that GlcA has a better effect on the overall conformation of GAGs ( Whitmore et al, 2020 ). In order to adapt to the ECM environment, the angle of the glycosidic linkages is allowed to change to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…To deal with the important issue of GAG length, which still represents a bottleneck and a challenge, different approaches have been described: the coarse-grained modeling approach, that has been applied to a library of heparin chains spanning from 6- to 68-mers [ 95 ]; dedicated algorithms have been developed to generate a library of non-sulfated chondroitin spanning from 10- to 200-mer which were compared to MD-generated ensembles for internal validation [ 84 ]; the same approach was applied to libraries of HA and non-sulfated dermatan, keratan and heparan [ 96 ]. …”
Section: Computational Studies Of Gags: What Has Been Done So Farmentioning
confidence: 99%
“…the same approach was applied to libraries of HA and non-sulfated dermatan, keratan and heparan [ 96 ].…”
Section: Computational Studies Of Gags: What Has Been Done So Farmentioning
confidence: 99%
See 1 more Smart Citation
“…It implies that computational approaches will be critical in understanding GAG structural biology and their mechanisms of interaction with their protein partners [ 35 , 36 , 37 ]. Significant progress has been made to investigate GAG structures, isolated and complexed with proteins, both at all-atom and coarse-grained levels [ 33 , 38 , 39 , 40 , 41 ]. However, appropriate tools for data mining of GAG-protein interactions are still missing [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%